The legal liability of hospitals - Retief, Maresa Cronje (University of the Free State, 1997)
This thesis presents an international legal comparative perspective on hospital liability law. The legal systems that are expounded on this subject are: the English law, the Australian law, the Canadian law, the law of the USA and the South African law. The health care systems of various countries are inspected. The hospital is researched in various contexts, and its historical development is researched. The health care system and hospital (setting) of the relevant legal systems are briefly discussed. It is apparent that every legal system that is discussed, has its own unique set of legal principles, legal doctrines and/or legal grounds which are implemented to establish hospital liability. No legal system acknowledges the same legal grounds nor follows the same approach towards hospital liability. The English hospital liability law acknowledges the following legal grounds: (i) Vicarious or indirect hospital liability; (ii) Direct hospital liability; (iii) Hospital liability in terms of the non-delegable duty. The English law is still setting the pace for most other countries. The Canadian law either acknowledges or implements the following legal grounds: (i) Vicarious hospital liability; (ii) Direct hospital liability; (iii) Breach of contract; (iv) The doctrine of ostensible agency is only recommended as a legal ground on which to found hospital liability, at this stage, but is not implemented by courts yet; (v) The non-delegable duty: The existence of this duty had been discussed but has not yet been implemented as an independent legal ground on which to found hospital liability. The Ontario Court of Appeal in Canada has held in Yepremian, that a hospital in Canada does not undertake a non-delegable duty to a patient, whether he presents himself at the hospital or not. On the other hand, there is also a tendency in Canadian hospital liability law, to call the direct duties of the hospital - in terms of its direct or corporate liability - non-delegable duties. The Australian hospital liability law has implemented: (i) Vicarious hospital liability; (ii) The non-delegable duty as an independent legal ground which founds hospital liability. However, the non-delegable duty has by such status as founding hospital liability, been referred to as direct liability. There is, however, no indepth discussion of any case law founded on direct liability as an independent legal ground based on fault in the Australian law, id est in the sense of the employer or institution's direct fault-based liability founded on the breach of its direct duty which induces direct negligence resulting in harm or injury. Most Australian decisions on hospital liability have been founded on the nondelegable duty. Australian courts have accepted that a hospital may undertake a non-delegable duty (of providing medical care) to its patients. The existence of the non-delegable duty has been accepted in various circumstances, although there is still a difference of opinion as to when the non-delegable duty exactly may arise. Hospital liability law in the USA has by far, presented the most developed and widest variety of legal grounds on which to found hospital liability. They acknowledge and implement: (i) Vicarious hospital liability; (ii) The doctrines of apparent agency and agency by estoppel; (iii) The direct or corporate liability of a hospital; (iv) Hospital liability in terms of the non-delegable duty. It is, however, unfortunate that some authors and some courts confuse the different independent legal grounds. Due to a lack of a scientific and a disciplined approach, concepts and requirements of distinct or specific legal grounds are not respected and kept apart, but confused. The South African hospital liability law only implements two legal grounds: (i) Vicarious hospital liability; and (ii) Breach of contract. Development of this area of the law is highly recommended.
Thesis (LL.D. (Criminal and Medical Law)) - University of the Free State, 1997
Keywords: Liability (Law) -- South Africa; Malpractice; Tort liability of hospitals -- South Africa